2016
DOI: 10.1111/ctr.12713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on hepatic ischemia–reperfusion injury in the setting of adult living donor liver transplantation

Abstract: Dexmedetomidine exerted protective effects against hepatic IRI during adult LDLiver transplantation, as indicated by suppression of ICAM-1, better scores of histopathological assessment, and augmented post-operative liver function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 94 publications
2
34
0
Order By: Relevance
“…The carbonic anhydrase inhibitor acetazolamide protects against cold hepatic IR injury by decreasing the MAPK signal and up‐regulating eNOS . Dexmedetomidine alleviates hepatic IR injury by suppressing intercellular adhesion molecule 1 and improving post‐operative liver function . Additionally, Chinese medicines have also been shown to conserve liver function in LT models.…”
Section: Pre‐conditions For Lt To Eliminate Cold Hepatic Ir Injurymentioning
confidence: 99%
“…The carbonic anhydrase inhibitor acetazolamide protects against cold hepatic IR injury by decreasing the MAPK signal and up‐regulating eNOS . Dexmedetomidine alleviates hepatic IR injury by suppressing intercellular adhesion molecule 1 and improving post‐operative liver function . Additionally, Chinese medicines have also been shown to conserve liver function in LT models.…”
Section: Pre‐conditions For Lt To Eliminate Cold Hepatic Ir Injurymentioning
confidence: 99%
“…Hepatic ischaemia–reperfusion injury is the major cause of liver injury, which is of clinical concern, especially following diverse hepatectomy and living donor liver transplantation. 1 Ischaemia–reperfusion injury, which involves complex inflammatory pathways, is a significant cause of liver damage and an important factor in a variety of diseases, injuries, and following transplantation surgery. 2 , 3 As liver ischaemia ends and reperfusion begins, oxidative stress is one of the first changes to take place and it regulates an oxidative stress-mediated apoptosis signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It applies its antiinflammatory effects by lowering the serum levels of catecholamines and releasing IL-10 and TNF-α (15). Fayed et al (10)found that DEX injection during anesthesia and after the completion of surgery for patients undergoing liver transplantation (LD Liver Transplantation) has a protective effect on hepatic ischemia-reperfusion injury (IRI), reduces the serum levels of lactate by facilitating the reperfusion of the transplanted tissue, facilitates the weaning and extubation of these patients and reduces their length of stay in ICU. In addition to the mechanisms mentioned in previous studies, other mechanisms of this drug in reducing the tissue ischemia are as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Administration of DEX exerted protective effects against hepatic ischemiareperfusion injury (IRI) in adult living donor liver transplantation. It results in suppression of ICAM-2, improved scores of histopathalogic assessment, and augmentation of live function tests after surgery (10). Patients with liver transplantation, have a high risk of post-surgery delirium.…”
Section: α2-mentioning
confidence: 99%